Development of Personal Selling Standard and Improvement of MSME X's Wedding Promotion Material - Radifan, Jamal; Suhaimi, Hasnul (Institut Teknologi Sepuluh Nopember, 2019)
Currently, the type of industry that still growing is the wedding industry. The increasing number of marriages in Indonesia contributes to the need for wedding services. MSME X owners seek the opportunities needed to provide services and various options for the needs of marriage. MSME X is currently held in Jakarta and Bekasi. This study discusses the business coaching process report MSME X personal selling and improving promotional materials in the form of brochures to attract consumers. The challenge in selling wedding services is that consumers cannot feel or touch services first. Preliminary analysis shows that salesperson use brochures as sales aids, there are differences in the level of sales competency among marketing employees, so personal selling activities are not optimal and affect the company's sales targets. Primary data collected through in depth interviews and observations, while secondary data is obtained from owners, the internet, and management books. The collected data will be analyzed using qualitative methods. This research focuses on the formulation of personal selling standards, and improvement of promotional materials as a tool for salesperson in conducting sales of wedding services. The results of this business coaching process explain the steps that can be used to conduct wedding service sales and the effect of improving promotional materials that help resolve limitations in the marketing aspects of MSME X